The design and implementation of geographic information systems - Harmon, John E. (J. Wiley, 2003)
Presents strategies for application development, interface design, and enabling Web-based access. Includes numerous case studies and examples from the private and public sectors. Provides information on integrating legacy MIS systems and planning for future developments in database design.